“Tiga Wajah” Financial Distress: Determinan, Pemediasi, dan Pemoderasi dari Praktik Manajemen Laba di Indonesia - Resi Ariyasa Qadri; Nilna Annisa Najiha (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
This study explicates the dynamic relationship between financial distress and earnings management using property and real estate companies listed in the Indonesia Stock Exchange from 2018 to 2020 as the unit analysis. The paper also aims to test whether financial distress can be positioned as a determinant, mediator, and moderator towards earnings management simultaneously. Structural Equation Modelling with Partially Least Square technique was used to analyzed data gathered from 90 financial reports of property companies. This research sheds a light on the use of silver-bullet analytical tools in form of the Partially Least Square method to produce robust results stronger than ordinary least squares. Researches on this issue were still scant. This study found that financial distress has a significant positive influence on earnings management practice and can mediate the negative relationship between earnings management practice and its determinants. The financial distress can also play a partial role as a moderator on the negative relationship between earnings management and its determinant. This research implicates that investors should pay more attention to the financial distressed property companies during the pandemic period because this research has proved the manager’s misbehaviour in increasing the earnings management practice of the financial distressed firms. Future research can adapt the proposed research model and test it with panel data regression procedures.